Programming of Stress-Sensitive Neurons and Circuits by Early-Life Experiences - Bolton, Jessica L.; Short, Annabel Katherine; Simeone, Kristina A.; Daglian, Jennifer; Baram, Tallie Z. (Frontiers in Behavioral Neuroscience, 2019)
Early-life experiences influence brain structure and function long-term, contributing to resilience or vulnerability to stress and stress-related disorders. Therefore, understanding the mechanisms by which early-life experiences program specific brain cells and circuits to shape life-long cognitive and emotional functions are crucial. We identify the population of corticotropin releasing hormone (CRH)-expressing neurons in the hypothalamic paraventricular nucleus (PVN) as a key, early target of early-life experiences. Adverse experiences, which are typically emotional rather than physical, increase excitatory neurotransmission onto PVN CRH cells, whereas optimal experiences, such as augmented and predictable maternal care, reduce the number and function of glutamatergic inputs onto this cell population. Altered synaptic neurotransmission is sufficient to initiate large-scale, enduring epigenetic re-programming within CRH-expressing neurons, associated with stress resilience and additional cognitive and emotional outcomes. Thus, the mechanisms by which early-life experiences influence the brain provide tractable targets for intervention.